Studies on the morphology of the olfactory organ in the freshwater teleost, Labeo bata (Hamilton - Ghosh , S.K.; Chakrabarti, P. (Mesopotamian Journal of Marine Sciences, 2022)
The structural components of the olfactory apparatus of Labeo bata (Hamilton, 1822) were studied morphologically as well as histologically. The oval shaped olfactory rosette was comprised of 24-26 lamellae of different sizes on each side of the median raphe. Histologically each lamella was composed of two layers of olfactory epithelium separated by narrow central core which made up of loose connective tissues, nerve fibres and blood vessels. The sensory olfactory epithelium contained principally three types of receptor cells: primary, secondary and microvillous cells. The non-sensory epithelium was typified with a series of mucous cells, stratified epithelial cells and mast cells. Basal cells were situated at the base of the epithelium, adjacent to the central core. Various cells on the olfactory epithelium were correlated with their functional consequence of fish concerned.